(untitled) - Cramer, Gail L. (New York, 1979)
A new edition of the classic text covering the structure and organization of agriculture through fundamental micro- and macroeconomics principles. It carefully develops such principles as consumer demand, price-determination in the market, and producer decision-making as they apply to all areas in the agricultural industry: marketing, policy development, financing, and more. Includes updated coverage of industry banking and finance, agricultural policy changes, plus the latest information on agriculture in the USSR and China. Also contains a new chapter providing a full treatment of macroeconomics and its relationship to the agricultural industry.
Keywords: Nông nghiệp,Agriculture; Khía cạnh kinh tế,Economic aspects